A review of recent trends in output, employment and productivity in Ireland - Sexton, J. J. (Statistical and Social Inquiry Society of Ireland, 2007)
This paper reviews real output, employment and productivity trends in the Irish economy over the ten year period from 1995 to 2005. The analyses, which are carried out within the framework of the CSO Annual National Accounts, extend across the entire economy. An important feature of the paper is the provision of estimated trend measures for different sectors, which entails an extension of the limited number of categories usually shown in the National Accounts statistics. As the measurement of volume or real economic output is the subject of ongoing discussion and debate at international level, it was considered appropriate to include a section which highlights some of the main methodological and conceptual problems involved, and how these are dealt with. Productivity trends, which are currently the subject of much debate, are analysed in some detail. These results reaffirm that productivity growth in the economy has faltered noticeably in recent years, due not only to declining productivity levels in some sectors (e.g. building and construction), but also due to ongoing changes in the sectoral composition of the economy. The paper also compares the recent output, employment and productivity performance of the Irish economy with the trends in the European Union and in the US. Finally, the paper reviews some policy options for the future, drawing particular attention to the consequences arising from declining productivity and the concentration of growth in a limited number of areas. The identification of possible areas which would underpin sustainable economic growth in the future is also discussed.
Read before the Society, 11 October 2006
Keywords: Output; Employment; Productivity; Economic growth; 314.15